Part-Whole-Modifiers and the *-Operator - Igel, Moritz (Proceedings of Sinn und Bedeutung, 2021)
In this paper, I present an analysis of German ‘ganz’ ( whole), which I see as evidence for the existence of the plural operator in the syntax as well as its ability to enter into scope relationships with other operators at LF. I also elaborate on more general ideas of ‘wholeness’ in natural language.